1993
DOI: 10.1530/acta.0.1280411
|View full text |Cite
|
Sign up to set email alerts
|

Detection of growth hormone, prolactin and human β-chorionic gonadotropin mRNA in growth hormone-secreting pituitary adenomas and in prolactin-secreting pituitary adenomas by in situ hybridization using a non-isotopic detection method

Abstract: DK. Detection of growth hormone, prolactin and human /J-chorionic gonadotropin mRNA in growth hormone-secreting pituitary adenomas and in prolactinsecreting pituitary adenomas by in situ hybridization using a non-isotopic detection method. Acta A non-isotopic in situ hybridization method with digoxigenin-labelled probes was used to examine growth hormone (GH), prolactin (PRL) and human \g=b\-chorionicgonadotropin (\g=b\-hCG(LH))gene expression in 63 pituitary tumours in acromegaly and 20 adenomas in hyperprola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The presence of hCG in pituitary adenomas has been described previously, although the numbers of cases studied were small and varying degrees of b-hCG expression were observed [13,16,19,23]. Using in situ hybridisation techniques, Levy and co-workers described b-hCG expression in 2 of 35 (6%) pituitary adenomas [7].…”
Section: Ki-67 Expressionmentioning
confidence: 85%
See 1 more Smart Citation
“…The presence of hCG in pituitary adenomas has been described previously, although the numbers of cases studied were small and varying degrees of b-hCG expression were observed [13,16,19,23]. Using in situ hybridisation techniques, Levy and co-workers described b-hCG expression in 2 of 35 (6%) pituitary adenomas [7].…”
Section: Ki-67 Expressionmentioning
confidence: 85%
“…The latter reports are consistent with our observations of relatively high rates of b-hCG expression in pituitary adenomas. These observations also suggest a greater sensitivity for the immunohistochemical technique in detecting b-hCG expression in pituitary adenomas [23]. Moreover, with double fluorescence labelling techniques, it has been demonstrated that the a and b-subunits of different glycoproteins are often expressed in separate adenoma cells [16].…”
Section: Ki-67 Expressionmentioning
confidence: 90%
“…This may be from separate cell populations as in the mixed GH/PRL cell adenoma or from the same cells as in the mammosomatotroph adenoma . In situ hybridisation studies indicate that co-expression of the two genes is even more common in these two tumour types than is suggested by immunocytochemistry (Li et al, 1993;Tallen et al, 1993;Yamada et al, 1994). In a further tumour, the acidophil stem cell adenoma, GH is co-expressed with PRL although it is rarely secreted in excess .…”
Section: Pituitary Adenomas Classical Pituitary Hormonesmentioning
confidence: 94%
“…The HCG ␤-subunit may be found in a variety of pituitary adenomas (Levy et al, 1994;Saccomanno et al, 1994;Tallen et al, 1993), but whether this has clinical relevance is unknown.…”
Section: Pituitary Adenomas Classical Pituitary Hormonesmentioning
confidence: 99%
“…Furthermore, the RNA:RNA hybrids are more stable than the DNA:DNA hybrids ( 4 3 . The method currently available for the generation of PRL RNA probes involves in-vim transcription of double-stranded DNA templates cloned in a specific orientation into a plasmid vector carrying bacteriophage DNA-dependant RNA polymerase promoters in its sequence (6).…”
Section: Wu Wang and Malarkeymentioning
confidence: 99%